The Current State of Education in Madagascar: Challenges and Solutions - Razanamiariso, Rakotomalala Nivomboahangy; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The first Missionary Station in Isoavina was established in the early years, with the initial school providing basic education and extracurricular activities, such as crafting, woodwork, and iron modeling, during the years 1870-1877. The school was known as the "Sekolin'ny Firenena" (National School). Education, in general, flourished under the guidance of foreign missionaries. However, when they departed, the school encountered several challenges. All activities experienced a significant decline due to the Malagasy teacher who continued the work lacking proper training. The school regained momentum with the inauguration of the new preschool "Manohisoa" on September 12, 1995, followed by the primary year 1 on September 10, 1997, and the Secondary year 2 on September 5, 2009, as stipulated in the authorization N2012/17-DREN ANALAMANGA on May 16, 2012. Regarding the performance in examinations, "MANOHISOA" School FJKM Isoavina had a 100% pass rate for CEPE (72.33%-74.44%-75.40% pass rates for CISCO Manjakandriana) in the academic years 2019-2020, 2020-2021, and 2021-2022, respectively. As for the BEPC, it was 56% for the year 2019-2020 (50.99% for CISCO), 100% for the year 2020-2021 (64.16% for CISCO), and 100% for the year 2021-2022 (74.23% for CISCO). Another 100% pass rate is achieved this 2022-2023 academic year. The disparity between public and church-affiliated schools poses a significant issue. Public schools have a considerably higher student population compared to their church-affiliated counterparts. Additionally, the number of teachers managing students in public schools is notably lower than those at MANOHISOA school (15 students per teacher). The inclusion of Holy Scripture curriculum in the educational program in FJKM schools helps to shape moral and ethical value to the students.